The Effect of Lead Pollution on GST, GPT, ALP, and Oxidant Stress in Fuel Stations - A. M. Ahmood; N. A. Ramdan; R. A. Hmza; R. S. Hassen (Journal of Madenat Alelem University College, 2013)
The study of the effect of lead pollution on the activity of GST GPT , and ALP was undertaken. Occupational workers. The spacemen of the project were divided in three groups according to their occupational period as follows: Group A: 15 workers ,period of occupation (2)yrs in Baghdad fuel station Group B: 15 workers, period of occupation(2-4) yrs in Baghdad fuel station Group C: 15 workers, period of occupation (5-8) yrs in Baghdad fuel station Another group of 15 healthy unexposed to lead were considered as control group. The results showed an elevation in the activity of all enzymes under investigation in the blood of workers. The activity was positively correlated with the period of occupation (i.e lead exposure). The elevation in GPT activity could be used as an indicator of liver damage , while elevated levels of GST occurs in all types of pollution to minimize the toxic effect of pollutant in erythrocytes and vital cells ,elevation in MDA related with the period of occupation (i.e lead exposure).